Atomic Structures of CH3NH3PbI3 (001) Surfaces - She, Limin; Liu, Meizhuang; Zhong, Dingyong (ACS nano, 2016)
We report on the atomic structures of methylammonium (MA) lead iodide (CH3NH3PbI3) perovskite surfaces, based on a combined scanning tunneling microscopy and density functional theory calculation study. A reconstructed surface phase with iodine dimers, coexisting with the pristine zigzag phase, was found at the MA–iodine-terminated (001) surfaces of the orthorhombic perovskite films grown on Au(111) surfaces. The reorientation of surface MA dipoles, which strengthens the interactions with surface iodine anions, resulting in a slight energy reduction of 34 meV per unit cell, is responsible for the surface iodine dimerization. According to our calculation, the surface MA dipoles weaken the surface polarity and are therefore considered to be stabilizing the surface structures.